2008
DOI: 10.3171/jns/2008/109/9/0454
|View full text |Cite
|
Sign up to set email alerts
|

Results using a self-expanding stent alone in the treatment of severe symptomatic carotid bifurcation stenosis

Abstract: Balloons may not be required to treat all patients with carotid stenosis. A stent alone was feasible in 79% of patients, and 79% of patients were alive and free from ipsilateral stroke or restenosis at 1 year. Restenosis rates with this approach are higher than with conventional angioplasty and stent insertion. Carotid arteries with very severe stenoses (> 90%) and circumferential calcification may be more successfully treated with angioplasty combined with stent placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…Previous studies reported that the perioperative clinical results were favorable despite postdilatation procedure. 6,7,18,19) However, few studies have examined the degree of stent expansion on follow-up. 8) In this study, we investigated stent expansion and changes et al 8) indicated that stent expansion was more marked in patients in whom a closed-cell stent with a weak radial force was used.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that the perioperative clinical results were favorable despite postdilatation procedure. 6,7,18,19) However, few studies have examined the degree of stent expansion on follow-up. 8) In this study, we investigated stent expansion and changes et al 8) indicated that stent expansion was more marked in patients in whom a closed-cell stent with a weak radial force was used.…”
Section: Discussionmentioning
confidence: 99%
“…6,18 This procedure is particularly effective for the treatment of postendarterectomy restenosis, 7 and, due to the avoidance of balloon angioplasty, it results in less hemodynamic instability. 5 Although progressive SES expansion can be seen up to 6 months postprocedure, 9 our results show that PCS is less likely to give a satisfactory longterm result in the presence of significant plaque calcification and the absence of soft plaque (PLAC score of B3 or 4).…”
Section: Discussionmentioning
confidence: 99%
“…Our technical and imaging follow-up protocols for CAS have been published previously. 6,18 We use an 8 × 40-mm SES to ensure good plaque coverage and maximal chronic outward force on the stenotic area. Our preference is to avoid the use of EPDs and balloons whenever the plaque morphology appears favorable on preoperative CTA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations